Dry eye symptoms align more closely to non-ocular conditions than to tear film parameters. Issue 8 (20th February 2015) - Galor, Anat; Felix, Elizabeth R; Feuer, William; Shalabi, Nabeel; Martin, Eden R; Margolis, Todd P; Sarantopoulos, Constantine D; Levitt, Roy C
Abstract : Objective: To evaluate the relationship between dry eye symptoms, non-ocular conditions and tear film parameters. Methods: Design : Cross-sectional study. Participants/setting : The study population consisted of patients who were seen in the Miami Veterans Affairs eye clinic. Patients filled out standardised questionnaires assessing dry eye symptoms (dry eye questionnaire 5 (DEQ5) and ocular surface disease index (OSDI)), non-ocular pain, depression and post-traumatic stress disorder (PTSD), and also underwent measurement of tear film parameters. Main outcome measures : Correlations between dry eye symptoms and non-ocular conditions as compared with tear film parameters. Results: 136 patients with a mean age of 65 (SD 11) years participated in the study. All correlations between the dry eye questionnaire scores (DEQ5 and OSDI) and (A) self-reported non-ocular pain measures (numerical rating scale and pain history), (B) depression and (C) PTSD were significant and moderate in strength (Pearson's coefficient 0.24 to 0.60, p<0.01 for all). All correlations between the dry eye questionnaires and tear film measures were weak (Pearson's coefficient −0.10 to 0.18) and most were not significant. Multivariable linear regression analyses revealed that PTSD and non-ocular pain more closely associated with dry eye symptoms than did tear film parameters. Specifically, non-ocular pain and PTSD accounted for approximately 36% of the variability in DEQ5 scores (R=0.60) and approximately 40% of variability in OSDI scores (R=0.64). Of note, none of the tear parameters remained significantly associated with dry eye symptoms in either model. Conclusions: Dry eye symptoms more closely align to non-ocular pain, depression and PTSD than to tear film parameters.